Effect of maternally-derived antibodies on the performance and immunity of broilers induced by in ovo or post-hatching immunizations with a live vaccine against infectious bursal disease - BC Michell; AD Gomes; NC Baião; M Resende; LJC Lara; NRS Martins (Brazilian Journal of Poultry Science, 2009)
The interference of low or high maternal antibodies titers on the attenuated infectious bursal disease (IBD) virus (IBDV) vaccine infection and its effects on the performance of broilers vaccinated at the 18th day of incubation (in ovo), at one day of age (subcutaneously-SC), or at 15 days of age (drinking water-DW) were investigated. After a series of three live vaccinations, breeders were given or not an IBD oil emulsion vaccine (IBD-OEV) prior to sexual maturity. At day 18 of incubation (in ovo), a commercial vaccine containing HVT and an intermediate IBDV strain or the single HVT vaccine was given. An intermediate IBDV vaccine was given SC at one day of age, or at 15 days of age via DW. The progeny of unvaccinated breeders presented higher neutralizing IBDVspecific antibody (IBDVab) titers at 25 and 40 days of age than those of the progeny of IBD-OEV breeders (p<0.05) at any broilers vaccination age and route. The lower IBDV RNA detection by RT-PCR in the bursa of Fabricius (BF) and the lower IBDV antibody titers in the serum of the groups vaccinated at one and 15 days of age derived from IBD-OEV breeders may indicate antibody-mediated IBDV neutralization. The inovo and one-day vaccinations did not interfere with performance, both in low and high antibody-titered progenies. The in-ovo vaccination against IBD is considered convenient and safe for industrial chickens, irrespective their maternal antibody levels.